Thermodynamic considerations for preventing the climate change - Arlt, Wolfgang (7th World Congress of Chemical Engineering, GLASGOW2005, incorporating the 5th European Congress of Chemical Engineering, 2005)
The climate change is related by most of the researchers to the increased content of CO in the terrestrial atmosphere. The primary choices for action are the reduction of the use of fossil energy by conservation and the use of in short time renewable energy. Before CO is sequestered, it has to be captured. For old power plants, the CO has to be removed from the flue gas by adsorption, absorption, or membranes. For new power plants, different thermodynamic cycles are possible. The demands to thermodynamics are presented. A novel absorption solvent is described and compared to the existing technology using amines or methanol. The use of energy and work for the separation process can only be predicted if the full power plant is simulated. This is an abstract of a paper presented at the 7th World Congress of Chemical Engineering (Glasgow, Scotland 7/10-14/2005).